Zeolites and Porous Materials: Insight into Catalysis and Adsorption Processes - Milojević-Rakić, Maja; Bajuk-Bogdanović, Danica (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Zeolites and Porous Materials: Applications in Catalysis and Adsorption Processes" provides a comprehensive exploration of the remarkable sphere of zeolites and porous materials, and their wide-ranging applications in catalysis and adsorption processes. Written by experts in the field, this Reprint offers a valuable resource for researchers, scientists, engineers, and students seeking to understand the fundamental principles, synthesis methods, characterization techniques, and cutting-edge applications of these materials. In addition to highlighting achievements and breakthroughs, this Special Issue Reprint addresses the current challenges and future directions in the field. It presents innovative strategies to overcome limitations and paves the way for new research and development opportunities. Furthermore, the Reprint emphasizes the significance of sustainability and green chemistry, demonstrating how zeolites and porous materials can contribute to a more sustainable and environmentally friendly future. Overall, "Zeolites and Porous Materials: Applications in Catalysis and Adsorption Processes" provides an up-to-date examination of zeolites and porous materials. With its diverse perspectives, and its emphasis on cutting-edge applications, this Reprint serves as an invaluable resource for anyone interested in understanding, utilizing, and pushing the boundaries of these exceptional materials.